Provide Student Knowledge About How Response On Growth Of Vetiver Seeds (Vetiveria zizanioides) In Saline Soil To Ascorbic Acid on Field Practice Learning of Plant Physiology - Aisar Novita; Suwandi Saragih; Efrida Lubis; Abdul Rahman Gemda; Fitria Fitria; Rini Susanti; Silvia Nora; Arie Hapsani Hasan Basri; Merlyn Mariana (JURNAL SERAMBI ILMU, 2021)
Vetiver root is a commodity that is tolerant enough to be planted in salty soils with a certain level of salinity. One approach to increase oxidative stress tolerance that will increase the enzyme substrate at the cellular level is ascorbic acid. The purpose of this study was to increase students' knowledge about how the response of vetiver seed (Vetiveria zizanioides) growth in salt soils to ascorbic acid through practical field learning in plant physiology courses. This research was conducted using a factorial randomized block design (RBD), the first factor was the salinity (S), namely S0: 0 dsm-1 and S1: 4 dsm-1. The second factor was ascorbic acid (A), namely A0: without treatment, A1: 50 ppm, A2: 100 ppm and A3: 150 ppm. There were 8 treatment combinations that were repeated 3 times resulting in 24 experimental units. The parameters observed were plant height, number of leaves and number of stomata. In this study, ascorbic acid had a significant effect on plant height, number of leaves and number of stomata. Saline soil had a significant effect on the number of stomata parameters. No interactions for all parameters were observed.